Impact Forecasting to Support Emergency Management of Natural Hazards. (6th October 2020) - Merz, Bruno; Kuhlicke, Christian; Kunz, Michael; Pittore, Massimiliano; Babeyko, Andrey; Bresch, David N.; Domeisen, Daniela I. V.; Feser, Frauke; Koszalka, Inga; Kreibich, Heidi; Pantillon, Florian; Parolai, Stefano; et al.
Abstract: Forecasting and early warning systems are important investments to protect lives, properties, and livelihood. While early warning systems are frequently used to predict the magnitude, location, and timing of potentially damaging events, these systems rarely provide impact estimates, such as the expected amount and distribution of physical damage, human consequences, disruption of services, or financial loss. Complementing early warning systems with impact forecasts has a twofold advantage: It would provide decision makers with richer information to take informed decisions about emergency measures and focus the attention of different disciplines on a common target. This would allow capitalizing on synergies between different disciplines and boosting the development of multihazard early warning systems. This review discusses the state of the art in impact forecasting for a wide range of natural hazards. We outline the added value of impact‐based warnings compared to hazard forecasting for the emergency phase, indicate challenges and pitfalls, and synthesize the review results across hazard types most relevant for Europe. Plain Language Summary: Forecasting and early warning systems are important investments to protect lives, properties and livelihood. While such systems are frequently used to predict the magnitude, location, and timing of potentially damaging events, they rarely provide impact estimates, such as the expected physical damage, human consequences, disruption of services, or financial loss. Extending hazard forecast systems to include impact estimates promises many benefits for the emergency phase, for instance, for organizing evacuations. We review and compare the state of the art of impact forecasting across a wide range of natural hazards and outline opportunities and key challenges for research and development of impact forecasting. Key Points: Probabilistic forecasts and rapid estimates of event impacts offer new possibilities for coping with damaging events in the emergency phase Developing impact forecasting that includes exposure and vulnerability estimates will tap into synergies across disciplines Extending single‐hazard to multihazard impact forecasts considering interactions between hazards and vulnerabilities is the next challenge